In Vivo Testing of the Semi-Closed Loop Infusion System: the Preliminary Observations - Andrijauskas, Audrius; Markevicius, Vytautas; Navikas, Dangirutis; Porvaneckas, Narunas; Andriukaitis, Darius; Stankevicius, Edgaras; Uvarovas, Valentinas; Sipylaite, Jurate; Kvederas, Giedrius; Gelzinis, Giedrius (Elektronika ir Elektrotechnika, 2015)
An In Silico testing of our novel automated clinical decision support system (ACDSS) in a prototype semi-closed loop (SCL) infusion system was previously reported. The decision making therein is based on the evaluation of hemodynamic and hemodilution parameters in compliance with an algorithm that implies interchangeable application of fluid infusion, vasopressor injection and red cell transfusion. Before starting the clinical validation trial, several amendments to the clinical algorithm were made on the basis of minor deficiencies revealed during an In Silico testing. For an intervention group in an on-going prospective randomised clinical trial, our prototype SCL infusion system is applied continuously for 12 perioperative hours in patients undergoing total hip replacement. This report describes our preliminary observations of the system’s performance in first 12 patients from an intervention group who completed the study. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.2458